Masa Kerja Tenaga Honorer Pada Satuan Kerja Perangkat Daerah (SKPD) - Rafly, Muhammad; Ruslie , Ahmad Sholikhin (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2024)
This research aims to find out and explain the working period for honorary workers who are in regional work units or SKPD. This research is a legal research by examining existing laws and regulations in Indonesia with legal materials from legislation to legal literature such as books and journals. Laws and regulations relating to the rules of honorary workers and length of service. This research resulted that the Regional Work Unit is a part of work that has scope in regional offices, sub-districts to sub-districts/villages where honorary workers are also included. The working period is calculated from the time the worker starts his job until the worker leaves the job. In government, government workers pay close attention to Law 5/2014 in determining the length of service. The conclusion of this study found that honorary workers tend to have a working timeframe least of one year and can be done continuously. Within the scope of work units the regional apparatus does not refer to the applicable rules. Honorary workers in regional apparatus work units are not or have not been regulated in Indonesian positive law, so that it is a legal vacuum.